How do students self-regulate? Review of Zimmerman’s cyclical model of self-regulated learning - Panadero, Ernesto; Alonso-Tapia, Jesús (Anales de Psicología / Annals of Psychology, 2014)
The use of learning strategies is crucial for students’ academic performance and promoting deeper learning approaches. The self-regulated learning models offer comprehensive theoretical backgrounds. These enable more holistic approaches to the use of learning strategies. In this paper, Zimmerman’s (2000; 2003; Zimmerman & Moylan, 2009) cyclical model of self-regulated learning is described and analysed as one of the most comprehensive. The model is grounded in social cognitive theory and is comprised of three phases (forethought, performance and self-reflection) with a special focus on the influences of motivation on self-regulation. The different processes included in the model are analysed here in detail. Zimmerman’s framework is considered in relation to other self-regulated learning models in order to recognize its importance in theory and practice.